3(3.8+-0.6y)+y=9

Simple and best practice solution for 3(3.8+-0.6y)+y=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3.8+-0.6y)+y=9 equation:


Simplifying
3(3.8 + -0.6y) + y = 9
(3.8 * 3 + -0.6y * 3) + y = 9
(11.4 + -1.8y) + y = 9

Combine like terms: -1.8y + y = -0.8y
11.4 + -0.8y = 9

Solving
11.4 + -0.8y = 9

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11.4' to each side of the equation.
11.4 + -11.4 + -0.8y = 9 + -11.4

Combine like terms: 11.4 + -11.4 = 0.0
0.0 + -0.8y = 9 + -11.4
-0.8y = 9 + -11.4

Combine like terms: 9 + -11.4 = -2.4
-0.8y = -2.4

Divide each side by '-0.8'.
y = 3

Simplifying
y = 3

See similar equations:

| .05=1.82/x | | -2y=4y-42 | | 64=-2(m+7)+m | | 63+7x=84+4x | | 4x-6x=12-20-5x | | 7x/2_x=0 | | 475+40+28h=601 | | 5x-3(4x-13)=81 | | 5(3.8+-0.6y)+3y=19 | | 16=4(v+1) | | 12n-9+2n-n=-87 | | 2w^2+6=-7w | | 5x-3(-5x-9)=127 | | 40=5ln(x-2)+6 | | 2w^2+6+7w=0 | | 7.95+4.35=60 | | -3x-6(3x+14)=147 | | -6x+4-3+x=11 | | 12-3=7(n-4)+5n | | (-14)(0.22)+(-16)(0.65)=(-18)(0.13) | | 8x+7y-3x= | | -2x-2(7x-16)=-10 | | 4y+4=-2x | | 14-4X=5=X/2 | | y-0.65y=3500 | | 7x+25*2=127 | | 40=2mxn | | 0.1x+x=2.75 | | 4x+32x+1=0 | | -4+5n=6 | | 3x-46x+1=0 | | n+17.9=18.3 |

Equations solver categories